2008
DOI: 10.3750/aip2008.38.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal differentiation in Atlantic cod, <I>Gadus morhua</I> L., and haddock, <I>Melanogrammus aeglefinus</I> (L.)

Abstract: . 2008. Gonadal differentiation in Atlantic cod, Gadus morhua L., and haddock, Melanogrammus aeglefinus (L.). Acta Ichthyol. Piscat. 38 (2): 127-133.Background. The purpose of this study was to determine the timing of gonadal differentiation in two gadoids: Atlantic cod, Gadus morhua L., and haddock, Melanogrammus aeglefinus (L.). This information is required to develop a practical protocol for the production of monosex populations of these species for aquaculture. Materials and Methods. Cultured larvae and ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…Our study provides evidence that morphological gonad differentiation in Atlantic cod occurs earlier in females than in males, as generally found in other primary gonochoristic teleosts [ 5 , 9 ]. Different from the results presented here, an earlier report described ovarian cavity formation in Atlantic cod at 27 mm TL [ 42 ]. This divergence might be related to significant growth differences between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study provides evidence that morphological gonad differentiation in Atlantic cod occurs earlier in females than in males, as generally found in other primary gonochoristic teleosts [ 5 , 9 ]. Different from the results presented here, an earlier report described ovarian cavity formation in Atlantic cod at 27 mm TL [ 42 ]. This divergence might be related to significant growth differences between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results confirmed that Atlantic cod is a differentiated gonochoristic species, where the sexually undifferentiated gonad develops directly into a testis or an ovary [42]. Our study provides evidence that morphological gonad differentiation in Atlantic cod occurs earlier in females than in males, as generally found in other primary gonochoristic teleosts [5,9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The timing of gonad development is a highly labile process both within (Maack et al, 2003;Melia et al, 2006;Wang et al, 2007) and among species (Devlin and Nagahama, 2002;Chiasson et al, 2008). Plasticity in the timing of gonad differentiation may be owing to differences among strains (e.g.…”
Section: Discussionmentioning
confidence: 99%